Modernization of an experimental installation and a procedure for investigating the anisotropic viscoelastic properties of composite materials at elevated temperatures - Martynenko, V. G.; Ulianov, Yu. N. (Інститут проблем машинобудування ім. А. М. Підгорного НАН України, 2018)
The paper describes the process of modernizing the existing installation designed for performing long-term tests of steel and aluminum cylindrical specimens for high-temperature creep. The modernization allowed conducting experimental studies of the anisotropic strength and viscoelastic characteristics of planar composite specimens at elevated temperatures. In order to reach the objective set, a scheme for reconstructing the specimen holders in the experimental installation was proposed, as well as the method of fixing them in the installation. The developed, designed and built automatic temperature control block for the electric furnace allowed maintaining elevated temperature with a sufficiently small error during its long use and controlling the heating temperature in a given range, which was necessary for studying the mechanical properties of composite specimens, as well as regulating the heating temperature in a given range. Conducting the experimental study of the instantaneous and long-term mechanical properties demonstrated the effectiveness of the improvements made for the experimental installation, as applied to the realization of such experiments.
Keywords: experimental investigation; relaxation curve; fiber-reinforced polymeric composite materials; long-term tests; high-temperature creep